2022
DOI: 10.1155/2022/7918596
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-641 Inhibits Endometrial Cancer Progression via Targeting AP1G1

Abstract: MicroRNA-641 (miR-641) was significantly decreased in various cancers, but its roles in endometrial cancer (EC) remain unclear. We explored the influences of miR-641 on the EC cells. In our study, the miR-641 expression was reduced in EC cells. Overexpression of miR-641 inhibited viability and proliferation of HEC-1A and HECCL-1 cells by CCK-8 and colony formation assays. Additionally, flow cytometry revealed that overexpression of miR-641 could remarkably promote apoptosis and arrest the cell cycle at the G1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In cell lines studies, overexpression of miR-641, miR-184, miR-302a-5p/367-3p, miR-152, and knockdown of miR1290 and miR-873 had inhibitory effects on EC cell viability and proliferation (132,146,148,149,163). MiR-135a downregulation and miR-320a/miR-424 expression decreased EC cell proliferation and migration (129,153).…”
Section: Ec and Tumor Suppressor Mirnamentioning
confidence: 99%
“…In cell lines studies, overexpression of miR-641, miR-184, miR-302a-5p/367-3p, miR-152, and knockdown of miR1290 and miR-873 had inhibitory effects on EC cell viability and proliferation (132,146,148,149,163). MiR-135a downregulation and miR-320a/miR-424 expression decreased EC cell proliferation and migration (129,153).…”
Section: Ec and Tumor Suppressor Mirnamentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%